2012
DOI: 10.1111/j.1742-4658.2012.08654.x
|View full text |Cite
|
Sign up to set email alerts
|

Sp1 and Sp3 are involved in the full transcriptional activity of centromere protein H in human nasopharyngeal carcinoma cells

Abstract: The overexpression of centromere protein H (CENPH), one of the fundamental components of the human active kinetochore, has been shown to be closely associated with human cancers. However, the mechanism of its transcriptional regulation has not been reported. The aim of the present study was to investigate the regulatory elements for the transcriptional regulation of CENPH in nasopharyngeal carcinoma cells. To characterize the CENPH promoter and identify regulatory elements, we cloned 1015 bp ()975 ⁄ +40 bp) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…We previously reported that Sp1 activates the transcription of Bmi1 and CENPH in nasopharyngeal carcinoma [32],[33]. Both Bmi1 and CENPH are oncogenes which are elevated in various malignancies originating in the breast, esophagus and nasopharynx [39]–[41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that Sp1 activates the transcription of Bmi1 and CENPH in nasopharyngeal carcinoma [32],[33]. Both Bmi1 and CENPH are oncogenes which are elevated in various malignancies originating in the breast, esophagus and nasopharynx [39]–[41].…”
Section: Discussionmentioning
confidence: 99%
“…We previously identified Sp1 as an important transcription factor for oncogenes in NPC, including B-lymphoma mouse Moloney leukemia virus insertion region 1 (Bmi1) and centromere protein H (CENPH), but the role of Sp1 in the development of NPC remains obscure [32],[33]. In the present study, we found the level of Sp1 was elevated in advanced NPC tissues and silencing of Sp1 significantly inhibited cell proliferation, clonogenicity, anchorage-independent growth and the stem-cell like phenotype of NPC cells, suggesting Sp1 as a potential therapeutic target for NPC.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these findings indicate that EGR1 plays an important role in gastrin‐induced upregulation of AE2 protein. In the case of the AE2 gene, SP1, as a ubiquitous transcription factor, may participate in basal transcription .…”
Section: Discussionmentioning
confidence: 99%
“…This construct was named pCDNA6-myc-HisB-MYC. An SP1 expression vector named pCDNA6-myc-HisB-SP1 was generated in our previous study [52]. All constructs were confirmed by direct sequencing.…”
Section: Plasmid Constructsmentioning
confidence: 99%
“…EMSA EMSA was performed as described previously [52]. Briefly, complementary oligonucleotide pairs containing either the putative binding site for Sp1 (Sp1 probe) or the mutant binding site for Sp1 (mutant Sp1 probe) were labeled with [ Wellesley, MA, USA).…”
Section: Immunohistochemistrymentioning
confidence: 99%